If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5u + -13 = -25 + -3u Reorder the terms: -13 + -5u = -25 + -3u Solving -13 + -5u = -25 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. -13 + -5u + 3u = -25 + -3u + 3u Combine like terms: -5u + 3u = -2u -13 + -2u = -25 + -3u + 3u Combine like terms: -3u + 3u = 0 -13 + -2u = -25 + 0 -13 + -2u = -25 Add '13' to each side of the equation. -13 + 13 + -2u = -25 + 13 Combine like terms: -13 + 13 = 0 0 + -2u = -25 + 13 -2u = -25 + 13 Combine like terms: -25 + 13 = -12 -2u = -12 Divide each side by '-2'. u = 6 Simplifying u = 6
| 9u-7+-8u=-2 | | 9u-7-8u=-2 | | 8x^4-42x^2+34=0 | | -3(4x-1)+9=27 | | 10x+y=50 | | (3x-1)(2x+5)=4x | | 5x+10=6-4x | | 2n+68=7n-2n-4 | | 2n^2=3n+5 | | 19+8= | | x/10=-15 | | x^2+14x+156=0 | | 3=s+14 | | 8w-7w+5=15-2 | | 9/10-21-41+3/4-11= | | 0.5=0.25-0.3x | | -1.2+3.5z=-4.7 | | 4y-1/7=4 | | -6y-1=-31 | | 4x-12=8x-12 | | 2x+x+8=44 | | 0.24*0.3= | | 9(X-13)=45 | | 2(n+4)=28 | | 7z+21=9z+10 | | 7z+21=10z-21 | | 2x-4(-7/11)=5 | | W-b=3forw | | -3x-1=-6x+23 | | 16x+13=4x-59 | | 4y-6=y+8 | | -3x+14=-11x+6 |